2018
DOI: 10.1111/sum.12401
|View full text |Cite
|
Sign up to set email alerts
|

What drives farmers to increase soil organic matter? Insights from the Netherlands

Abstract: Soil organic matter (SOM) is an important resource base for arable farming. For policies on SOM to be effective, insight is needed on why and under which conditions farmers are willing to increase SOM content. This study used the theory of planned behaviour to analyse what prevents or encourages Dutch farmers to increase the SOM content of their fields. In an online survey, 435 arable farmers were asked questions to understand their attitude (perceived benefits), subjective norm (social pressure) and perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 30 publications
1
20
2
Order By: Relevance
“…Similarly, Mullins (1999) suggested a threshold of 2% SOM, below which the soil would be vulnerable to cohesion and degradation. Our finding suggests a possible mechanism for avoiding risks of land degradation by increasing ¼ of the critical level of SOM in five years, even though SOM content is highly reliant on ❖ www.esajournals.org 9 February 2020 ❖ Volume 11(2) ❖ Article e03028 soil management practices (Hijbeek et al 2018). In turn, the positive effect of nitrogen on soil organic carbon can be traced to increased net primary production improving vigor of plants and gives a boost to SOM turnover.…”
Section: Improvement In Soil Fertilitymentioning
confidence: 79%
“…Similarly, Mullins (1999) suggested a threshold of 2% SOM, below which the soil would be vulnerable to cohesion and degradation. Our finding suggests a possible mechanism for avoiding risks of land degradation by increasing ¼ of the critical level of SOM in five years, even though SOM content is highly reliant on ❖ www.esajournals.org 9 February 2020 ❖ Volume 11(2) ❖ Article e03028 soil management practices (Hijbeek et al 2018). In turn, the positive effect of nitrogen on soil organic carbon can be traced to increased net primary production improving vigor of plants and gives a boost to SOM turnover.…”
Section: Improvement In Soil Fertilitymentioning
confidence: 79%
“…To the best of our knowledge, no study investigated these aspects for agronomic management to reduce FHB and mycotoxins in wheat before. Two related studies showed that the belief 'increase in soil fungi' was negatively related to an attitude to increase soil organic matter in the Netherlands [35]. And the belief 'Increase risk of fungal diseases' was not a significant driver to adopt incorporation of crop residue in the soil (a well-known measure against Fusarium species infection), as surveyed among Italian farmers [36].…”
Section: Discussionmentioning
confidence: 99%
“…This latter analysis was extended with an assessment of the robustness of the belief results, because the statistical validity of the standard analysis of the TPB beliefs has been questioned, i.e. the so-called expectancy-value muddle [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The European soil map (European Commission, 2012) shows that Brandenburg has coarse soils with a clay fraction <18% and a sand fraction >65%. In combination with high-intensity arable farming and large field sizes (>50 ha) these sandy soils are prone to losing soil organic C from topsoil and wind erosion (Hijbeek et al, 2014), especially in fallow periods. The German Ministry for Food and Agriculture therefore recommends maintaining a soil coverage ration above 25% throughout the year, by applying cover cropping and undersowing (BMELV, 2013).…”
Section: Methodsmentioning
confidence: 99%